Entropy-cooled nonequilibrium states of the Hubbard model - Werner, Philipp; Li, Jiajun; Golez, Denis; Eckstein, Martin (Physical Review B, 2019)
We show that the recently proposed cooling-by-doping mechanism allows one to efficiently prepare interesting nonequilibrium states of the Hubbard model. Using nonequilibrium dynamical mean field theory and a particle-hole symmetric setup with dipolar excitations to full and empty bands we produce cold photodoped Mott insulating states with a sharp Drude peak in the optical conductivity, a superconducting state in the repulsive Hubbard model with an inverted population, and eta-paired states in systems with a large density of doublons and holons. The reshuffling of entropy into full and empty bands not only provides an efficient cooling mechanism, it also allows one to overcome thermalization bottlenecks and slow dynamics that have been observed in systems cooled by the coupling to boson baths.
CRIS-Team WoS Importer:2019-10-25